Variability in Rhizoctonia solani(AG-1 IA) isolates causing sheath blight of rice in India - and C.S. REDDY, K. SUSHEELA* (Indian Phytopathology, 2013)
Variability in 35 isolates of Rhizoctonia solani KÃ¼hn [Teleomorph: Thanatephorus cucumeris (Frank) Donk] causing sheath blight of rice and weeds, was examined by polymerase chain reaction-random amplified polymorphic DNA (PCR-RAPD) analysis in conjunction with morphology and pathogenicity studies. Studies on morphological characterization of R. solani isolates showed that isolates were highly variable both in mycelial and sclerotial parameters, with no consistent characters related to virulence, origin, production system or geographic origin. Pathogenicity of R. solani was also evaluated and based on their virulence, isolates were classified into different virulent groups. The similarity values of RAPD profiles ranged from 0.37 to 0.85 with an average of 0.61 among all the isolates. The percentage polymorphism detected per primer varied from 76.9 to 100% which suggested their utility in DNA finger printing of the sheath blight isolates. Relation between cultural/morphological characteristics, aggressiveness and genetic variation based on RAPD markers, and possible reasons for high intra-group variability are discussed.